Challenges and Lessons Learned to Improve the Deaf User Experience: Compliance with ABNT NBR 17060 Standard in Mobile Applications - Aguiar, Ana Carolina; Melo Alves, Lucas Eduardo; Lima, Pedro; Costa Aguiar, Yuska Paola; Maritan, Tiago; Omaia, Derzu (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
The VLibras Mobile Application is a translation tool from Brazilian Portuguese to Libras (Brazilian Sign Language) using an Avatar in 3D animation. The tool provides deaf people a means of accessing textual content based on animation in Libras. Furthermore, VLibras can be used as a communication tool between deaf people, Libras interpreters, and people in general (interested in learning Libras, for example). In this context, having access is not the same as being accessible. Thus, it is essential to improve the deaf user experience through the compliance of VLibras Mobile with ABNT NBR 17060 Standard. The assessment was conducted for all VLibras Mobile screens and features, covering the totality of criteria of the standard. Analogous to the WCAG standard, the NBR 17060 Standard also considers three accessibility levels (A: mandatory, AA: minimally accessible, and AAA: optional), as well as the four principles (Perceptible, Operable, Understandable, and Robust). It also included the standard categories: Perception and Comprehension, Control and Interaction, Media, and Coding. The goal was to compile a general overview of VLibras Mobile compliance with the standard to know this quality regarding accessibility. Also, the analysis allowed identifying an ensemble of non-compliance criteria, both located on a specific screen or across the application. These were transcribed as 12 issues with their respective severity level and reported to developers to improve VLibras Mobile accessibility. Also, the specific audience of VLibras, deaf people, led to classify a group of criteria as non-applicable. The results revealed that the most important features of VLibras, Traduction and Home, demonstrated higher compliance rates. However, the screen Customization showed significant non-compliance. Overall, the issues reported are of low severity, and their correction has a transversal impact on the application. This text is an experience report of the assessment conducted, its challenges, results, and lessons learned.